Role of Islamic Finance in Supporting Economic Recovery in Nigeria Post-Covid-19 Pandemic - Abdulkareem, Ibraheem Alani; AbdulGaniyy, AbdulFattah; Mahmud, Mohd Sadad (Institut Agama Islam Negeri Kendari, 2022)
Since the deadly infection pandemic episode toward the end of 2019, more than 200 countries have been impacted. One of the most significant impacts of the pandemic that is undeniable is the increase in the intensity of poverty around the world. It is a health sector crisis, and the virus is also causing an economic meltdown. Various nations fall into recession, and more people live beneath the poverty level. The pandemic is causing both health and economic crises. This study examines the potential of Islamic finance in supporting economic recovery in the post-Covid-19 pandemic. The method reviews previous studies, including journal articles, research papers, policy documents, and reports in related fields to support this study. Based on past studies, the study document that Islamic finance via Mudarabah, Sukuk, Musharakah, Qard al-Hasan, Sadaqat, waqf, and Islamic Microfinance has essential to support economic recovery in a post-Covid-19 pandemic in society. In particular, the study found that Islamic finance is positively associated with a reduction in the impact of the pandemic on the people and the whole world economy. The study has added to the body of knowledge by looking at the role of Islamic finance in terms of the effect of the Covid-19 pandemic on the economy and society. The study has implications for the financial institutions, policymakers, and government in terms of adopting Islamic finance products and principles to address the effect of the Covid-19 pandemic crisis on the economy, thereby improving the social well-being of the people and improving the global economy.